Integrasi Sistem Single Submission Pengangkut Pada Proses Clearance Kapal Berbasis Analisis IPA (Importance-Performance Analysis) oleh PT. Trans Cakrawala Perkasa - Dzaky Kasparuma; Trisnowati Rahayu; Rizqi Aini; Sri Mulyanto H (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
The quality of digital system services in the ship clearance process is closely related to the work effectiveness of shipping agency companies. The advancement of port operational services is influenced by the system’s ability to provide convenience, speed, accuracy, and service integration for users. The system used in the ship clearance process must be able to meet user needs and support inter-agency coordination so that ship services can operate more effectively and efficiently. This study aims to analyze the performance level and the level of user importance regarding the implementation of the Single Submission Pengangkut System in the ship clearance process at PT Trans Cakrawala Perkasa. The research employed a descriptive quantitative approach with a sample of 30 respondents consisting of ship agents involved in the clearance process. Data were collected through questionnaires, observations, and literature studies. The data were analyzed using validity tests, reliability tests, conformity level analysis, and the Importance Performance Analysis (IPA) method. The results indicate that the SSM Pengangkut System has made a positive contribution to accelerating document processing, facilitating system usage, increasing work productivity, and supporting coordination among related agencies. Based on the IPA Cartesian diagram, one indicator was identified as a priority for improvement, while other indicators were categorized as maintain performance, low priority, and high performance with lower importance levels. Overall, the implementation of the Single Submission Pengangkut System has been running quite well; however, continuous evaluation and improvement are still needed to optimize the ship clearance process further.